2010
DOI: 10.1111/j.1467-7687.2010.00998.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracking and quantifying objects and non‐cohesive substances

Abstract: The present study tested infants' ability to assess and compare quantities of a food substance. Contrary to previous findings, the results suggest that by 10 months of age infants can quantify non-cohesive substances, and that this ability is different in important ways from their ability to quantify discrete objects: (1) In contrast to even much younger infants' ability to discriminate discrete quantities that differ by a 1:2 ratio, infants here required a 1:4 ratio in order to reliably select the larger of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 57 publications
1
43
0
Order By: Relevance
“…(i.e., 2 − 1 =?). Infants within these paradigms are remarkably good at doing simple addition, subtraction, and comparisons (Gallistel and Gelman 1992;Gilmore et al 2007;McCrink and Wynn 2004;Van Marle and Wynn 2011;Wynn 1998aWynn , 1998bXu and Spelke 2000). Infants can also perform matching to samples (Xu and Garcia 2008).…”
Section: What About Infants and Children?mentioning
confidence: 99%
“…(i.e., 2 − 1 =?). Infants within these paradigms are remarkably good at doing simple addition, subtraction, and comparisons (Gallistel and Gelman 1992;Gilmore et al 2007;McCrink and Wynn 2004;Van Marle and Wynn 2011;Wynn 1998aWynn , 1998bXu and Spelke 2000). Infants can also perform matching to samples (Xu and Garcia 2008).…”
Section: What About Infants and Children?mentioning
confidence: 99%
“…However, the perceptual properties of the referent over the morphosyntactic properties of the noun modulate its interpretation as an object or a substance; a linguistic label of mass or of count assigned to the referent is not necessary to define it as an object or a substance (Soja, 1992). Moreover, some studies have found that the ability to discriminate objects from substances, at least for what concerns their tracking and quantification, is prelinguistic and present by at least 10 months of age (i.e., before most children are producing their first words; Hespos, Ferry, & Rips, 2009;vanMarle & Wynn, 2011; for a review, see Hespos & vanMarle, 2012). However, some specific cognitive biases in early word learning seem to favor objects over substances.…”
Section: Morphological Number Conservation Operations Countabilitymentioning
confidence: 99%
“…Using procedures similar to Feigenson et al (2002), a study found that 10- to 12-month-olds were equally successful at choosing the larger amount of discrete food items with a set that was below (1 vs. 2) and above (5 vs. 10) the capacity limit predicted by object-based individuation models (Van Marle and Wynn, 2011). This result suggests that an approximate representation system is at work when responding to quantitative order.…”
Section: Ordinal Basis Of Relative Quantity Judgmentmentioning
confidence: 99%
“…The parallel that exists between cardination and ordination means that repeated assessments about whether two quantities are different or the same in size are governed by the same representation systems as repeated assessments about whether one numerical set is larger or smaller than another set. Unfortunately, only one infant study has broached the topic of large set RQJs (Van Marle and Wynn, 2011) so it remains to be seen whether the same pattern holds for our youngest counterparts.…”
Section: Ordinal Basis Of Relative Quantity Judgmentmentioning
confidence: 99%